Can democracy aid improve democracy? The European Union's democracy assistance 2002–2018. Issue 5 (4th July 2022) - Gafuri, Adea
ABSTRACT: Although Western donors allocate billions of dollars each year to democracy assistance, the role of such assistance in democratization processes remains contested. This paper is the first to capture the influence of European Union-led democracy assistance projects across 126 recipient countries. Using panel data, the analysis carried out employs democracy assistance data extracted from the OECD Crediting Reporting System for all the available years at the time of writing, i.e. 2002–2018, and data from the Varieties of Democracy Institute to capture democracy levels. The study finds that EU's democracy assistance positively impacts democracy levels of recipient countries. The EU is one of the largest and most credible promoters of democracy worldwide, and I argue that its democracy assistance can be successful because it is coupled with political conditionality and monitoring mechanisms in the beneficiary countries.